A Commentary on Plato's Ion - Oates, William (My University, 2003)
This study focuses on testing the five hermeneutic principles set out by Jakob Klein and two ofmy own. The test consists ofwriting a commentary on Plato's Jon read in accordance with those principles. In summary these principles require paying close attention to the dramatic aspect ofthe dialogue and reading in a very detailed fashion. The success or failure ofthe principles is to be decided on the basis ofthe quality ofthe reading they produce. If following the principles produces a more comprehensive and deeper understanding of the dialogue then they should be deemed successful. The principles require that attention be given to the framing details of the dialogue and that an attempt be made to integrate them into the overall understanding. This interpretation thus reaches a somewhat different understanding of Sokrates' purpose in talking to Ion and Plato's purpose in writing the dialogue. Instead ofan abstract battle between philosophy and poetry, we have a battle between two particular characters over a real city.
Keywords: hermeneutic, principles, commentary, principles, comprehensive, understanding, Plato, ion, poetry, philosophy